STRATEGY TO INCREASE THE COMPETITIVENESS OF LOCAL VEGETABLES AGAINST IMPORTED VEGETABLES IN PEKANBARU CITY, RIAU: A REVIEW OF CONSUMER LOYALTY - Mery Berlian, Abdul Wahib Muhaimin, Nuhfil Hanani, Silvana Maulidah, (Chelonian Research Foundation, 2024)
One nutritional element that is crucial for good health is vegetables. The body needs a variety of nutrients, including vitamins, minerals, and fiber, which are found in vegetables. Local and imported veggies are the two categories of vegetables that are often consumed in Indonesia. Finding out what factors affect consumers' loyalty to imported and local veggies is the aim of this study. This study employs a comparative methodology and quantitative research techniques. In this study, questionnaires, observations, and literature reviews were used as data gathering methods. The SPSS software is then used to examine the data that has been gathered. The findings demonstrated that the elements most influencing consumer loyalty to local and Keywords:Consumer: Competitiveness , Local Vegetables, Imported Vegetables